A comparative study of Environment Risk Assessment (ERA) guidelines of developing and developed countries including Bangladesh - Mimmi, Syeda Fahria Hoque (Brac University, 2021)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2021.